2021
DOI: 10.1016/j.jtherbio.2021.103002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraspecific variation on measurements of thermal tolerance in bumble bees

Abstract: Climate change is an important driver of bee decline despite the fact that many species might respond to climate change differently. One method to predict how a species will respond to climate change is to identify its thermal tolerance limits. However, differences in thermal tolerance might also occur among distant populations of the same species based on their local environment or even among castes of social insects. Here, we investigated intraspecific differences in thermal tolerance among subspecies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 51 publications
1
32
1
Order By: Relevance
“…Different threats have been identified to explain the global decline of bumblebees. For several years, many studies have explored effects of microbiota, diet, temperature, and pesticide exposure on bumblebee's health in lab conditions (Gill and Raine, 2014;Vanderplanck et al, 2019;Barraud et al, 2020;Rothman et al, 2020;Maebe et al, 2021a;Oyen et al, 2021). However, most of these studies used commercially available bumblebee species (i.e., Bombus impatiens in North America and B. terrestris in Europe, and Bombus hypocrita in Asia) which are known to be tolerant and resistant to environmental changes (Oyen and Dillon, 2018;Maebe et al, 2021b;Martinet et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Different threats have been identified to explain the global decline of bumblebees. For several years, many studies have explored effects of microbiota, diet, temperature, and pesticide exposure on bumblebee's health in lab conditions (Gill and Raine, 2014;Vanderplanck et al, 2019;Barraud et al, 2020;Rothman et al, 2020;Maebe et al, 2021a;Oyen et al, 2021). However, most of these studies used commercially available bumblebee species (i.e., Bombus impatiens in North America and B. terrestris in Europe, and Bombus hypocrita in Asia) which are known to be tolerant and resistant to environmental changes (Oyen and Dillon, 2018;Maebe et al, 2021b;Martinet et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…These objective measures are helpful in determining the physiological vulnerability of a species to climate change and to predict species responses to thermal stress (Burdine & McCluney, 2019; Deutsch et al, 2008; Hamblin et al, 2017; Kellermann et al, 2012). However, it seems that thermal sensitivity in bumblebees is species‐specific (Hamblin et al, 2017; Martinet, Dellicour et al, 2021; Martinet, Zambra et al, 2021; Oyen et al, 2016; Zambra et al, 2020), and even intraspecific variation between subspecies and castes has been reported (Maebe et al, 2020). Furthermore, Penick et al (2016) note that the negative effects of temperature extremes can be observed before the limits of CT MIN and CT MAX are reached while selection for thermal tolerance strongly depends on rare but extreme thermal events.…”
Section: Physiologymentioning
confidence: 99%
“…As with most insects, cold temperatures in bumblebees induce a typical sequence that starts with slowed behavioural responses and impaired coordination before a burst of muscle activity, followed by total paralysis in a chill coma (e.g. Maebe et al, 2020; Oyen & Dillon, 2018). Although the mechanisms for this response have not been investigated in bumblebees, they are likely to be very similar to those described in other insects.…”
Section: Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Both holobiont partners (i.e., bees and microbiome) contribute to its plasticity: the microbiome is primarily involved in processing food, toxins and promoting immunity, while the bee host contributes to thermal tolerance and mobility. Some bee species seem to be able to face environmental changes through plasticity in their thermoregulation (e.g., Martinet et al, 2021a,b), thermal tolerance (Maebe et al, 2021a), phenology (Duchenne et al, 2020;Gérard et al, 2020a), size (Gérard et al, 2020b(Gérard et al, , 2021, nesting behavior (Ghisbain et al, 2021) or diet (Scheper et al, 2014), which might partly explain their contrasting population trends (reviewed by Maebe et al, 2021b).…”
mentioning
confidence: 99%